Study of heart rate variability test in prediabetes, prehypertension and co-existing prediabetes with prehypertension subjects - Maharjan, Sanjay; Maharjan, Shreekrishna; Pathak, Aastha; Gurung, Sanyukta; Poudyel, Pragati; Byanju, Jayandra; Shrestha, Ira (Journal of Patan Academy of Health Sciences, 2025)
Introduction: Cardiac autonomic neuropathy is common in people with diabetes and hypertension and increases the risk of heart disease. Heart rate variability (HRV) is a reliable method to assess cardiac autonomic function. However, limited information exists about HRV changes before these conditions develop. This study aimed to assess HRV changes in individuals with prediabetes, prehypertension, and both conditions together. Method: A comparative cross-sectional study was conducted on 120 participants (both sexes, mean age 40.24±7.34 years) after ethical approval. Participants were categorized into four groups (n=30 each): control, prediabetes, prehypertension, and coexisting prediabetes with prehypertension, based on HbA1c and blood pressure measured on two occasions. HRV was recorded for 5 minutes in the sitting position using the Polar H10 device, and time- and frequency-domain parameters were analyzed and compared with controls. Result: Total Power was significantly lower in the coexisting group and prehypertensive group compared to controls (p<0.001). Time-domain indices- RMSSD, NN50, pNN50, and SDNN were also markedly reduced in the coexisting and prehypertensive groups compared to controls (p<0.001 for all). The mean RR interval was shorter in the coexisting group (p<0.001), indicating a higher resting heart rate. Maximum and minimum heart rates were also significantly higher (p = 0.032 and 0.002, respectively). HRV parameters showed no significant difference between the prediabetes and control groups. Conclusion: HRV was lowest in the coexisting group, moderately reduced in prehypertension, and unchanged in prediabetes. Coexistence of prediabetes and prehypertension causes greater autonomic dysfunction, highlighting the importance of early detection and prevention.